Reviving Learning: Ventriloquism Based Instructional Innovation In Interactive Learning Design - Edy Rakhmadi; Norliani; Muhammad Muhaimin; Suhaimi; Muhammad Saleh (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study investigates the implementation of ventriloquism as an innovative instructional strategy in classroom learning at SMP Negeri 2 Kotabaru. Employing a qualitative case study approach, the research aims to explore how ventriloquism functions as an interactive pedagogical method and to examine its impact on student engagement, confidence, communication skills, and learning outcomes. Data were collected through in-depth interviews, participant observation, and document analysis involving teachers, students, and school stakeholders. The findings reveal that ventriloquism-based instruction significantly enhances student engagement and participation by transforming passive classroom dynamics into active and dialogic learning environments. Students demonstrated increased confidence in expressing ideas, reduced anxiety in speaking, and improved communication skills through interactions with the puppet. The use of character-based dialogue and storytelling also contributed to stronger conceptual understanding and better knowledge retention. Additionally, ventriloquism fostered a positive and inclusive classroom atmosphere, promoting emotional safety and collaborative learning. From the teacher’s perspective, the innovation stimulated creativity and reflective practice, encouraging more engaging instructional design. The study concludes that ventriloquism represents a low-cost, flexible, and culturally relevant instructional innovation aligned with the goals of the Merdeka Curriculum, particularly in supporting student-centered learning and character development. Despite challenges related to training and curriculum constraints, ventriloquism shows strong potential as a scalable pedagogical strategy for enhancing learning quality in Indonesian classrooms